1987
DOI: 10.1152/ajpheart.1987.252.6.h1211
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte and endothelial injury with ischemia reperfusion in isolated rat hearts

Abstract: We determined the time course of ischemic injury, the effects of reperfusion, and the protective effects of prostacyclin, oxygen radical scavengers, and diltiazem on myocardial myocyte and endothelial cell functions in isolated rat hearts. Left ventricular power and coronary microvascular permeability were used as indexes of myocyte and endothelial cell function, respectively. Neither 5- nor 10-min ischemia reperfusion significantly changed power or permeability. However, with reperfusion following 20 and 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Additionally, I/R may cause injury through the recruitment of proinflammatory leukocytes. Endothelial cells represent the first cell type injured by reactive oxygen species generated during I/R (30). In vitro, the mechanisms of endothelial cell death caused by H/R remain poorly understood and may involve both necrotic and apoptotic forms of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, I/R may cause injury through the recruitment of proinflammatory leukocytes. Endothelial cells represent the first cell type injured by reactive oxygen species generated during I/R (30). In vitro, the mechanisms of endothelial cell death caused by H/R remain poorly understood and may involve both necrotic and apoptotic forms of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…H/R, which generates cytotoxic reactive oxygen species and promotes the recruitment of inflammatory leukocytes, causes lung injury and cell death involving both necrotic and apoptotic events. Endothelial cells appear to be the first cell type injured by reactive oxygen species generated during I/R (19). The mechanisms of apoptotic cell death induced by H/R, however, are not well understood, especially in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreating heart with nisoldipine could prevent the macromolecular leakage after ischemia [26]. Sunnergren et al [27] reported that reperfusion following 20 and 30 min of ischemia resulted in a reduction of contractile power by 50 and 60%, and increase of permeability by 70 and 90%. If the heart underwent 30 min of ischemia, the increase in permeability was evident after 4 min reperfusion and further exacerbated at 20 min.…”
Section: Discussionmentioning
confidence: 99%